Diversidad de la micobiota endófita de Cattleya percivaliana y Cattleya trianaei cultivadas en invernadero (2015)
ABSTRACT: Endophytic microorganisms are characterized by asymptomatic development inside tissues. In this study we isolated endophytic fungi of leaves and roots from Cattleya percivaliana and Cattleya trianaei grown under greenhouse conditions. We isolated 323 endophytic fungi from 4,800 tissue fragments: these isolates were classified into 14 genera characterized macroscopically and microscopically, and ve morphotypes could not be identified. A higher number of individuals of C. trianaei were colonized by fungi, and a higher diversity of endophytes were found in leaves. Some genera exclusively colonized one tissue, or both tissues. In leaves, we registered Chromelosporium, Cladosporium, Exophiala, Gonatobotrys, Monilinia, and Nodulisporium while Curvularia, Gloeosporium, and ve unidentified morphotypes only colonized roots. The genera Aureobasidium, Botryotrichum, Colletotrichum, Fusarium, Sclerotium, and Trichoderma grew on both tissues. Fusarium was the most abundant genus in roots and, Colletotrichum and Sclerotium in leaf tissue.